If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + -6 = b + 3(b + 2) Reorder the terms: -6 + 6b = b + 3(b + 2) Reorder the terms: -6 + 6b = b + 3(2 + b) -6 + 6b = b + (2 * 3 + b * 3) -6 + 6b = b + (6 + 3b) Reorder the terms: -6 + 6b = 6 + b + 3b Combine like terms: b + 3b = 4b -6 + 6b = 6 + 4b Solving -6 + 6b = 6 + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. -6 + 6b + -4b = 6 + 4b + -4b Combine like terms: 6b + -4b = 2b -6 + 2b = 6 + 4b + -4b Combine like terms: 4b + -4b = 0 -6 + 2b = 6 + 0 -6 + 2b = 6 Add '6' to each side of the equation. -6 + 6 + 2b = 6 + 6 Combine like terms: -6 + 6 = 0 0 + 2b = 6 + 6 2b = 6 + 6 Combine like terms: 6 + 6 = 12 2b = 12 Divide each side by '2'. b = 6 Simplifying b = 6
| 4x-2(x-3)=-9+5x+3 | | 3x+8=-87-7x | | w^2+6w-27=0 | | 313x=15 | | 6x+12x=30x+60+3 | | n+(n+2)=92 | | n+(n+3)=92 | | 5x+18=3+7x-5 | | 5n+2(n+2)=18-7n | | -x/7.8=5.8 | | (11t+6)(5t-15)=0 | | 1/2d-5=6 | | 18x+18=180 | | 154-12x=35+14x | | 154-12x=35+13x | | 4+10x=180 | | 154-12x=35+12x | | (x+1)(5-4)=0 | | 6(x-24)=1(x+26) | | -34+7n=-8(-5n-4) | | 4z+76= | | x^4-2x^3-17x^2+4x+30=0 | | -12+m=17 | | -3.8y-1.6=-9.998 | | 9y+3-5y=13 | | 114-2x=16x-16 | | -13-6=5-9x | | a^2-13a-90=0 | | 6r-7=-(1-5r)+2 | | 14+28x=42+18x | | -10y-1+4y=-4 | | 1.75=-5(k-0.75) |